Methyl isocyanate: reproductive and developmental toxicology studies in Swiss mice. - Schwetz, B A (1987)
Studies were conducted in Swiss (CD-1) mice to evaluate the potential of inhaled vapors of methyl isocyanate (MIC) to affect reproduction and development. Inhaled MIC at concentrations of 0, 1, or 3 ppm, 6 hr per day during days 14 through 17 of gestation caused a significant increase in the number of dead fetuses at birth and caused a significant decrease in neonatal survival during lactation. In contrast, exposure of male and female mice to 1 or 3 ppm given 6 hr per day for 4 consecutive days had no effect on reproduction during mating trials conducted 1, 8, and 17 weeks after the exposure period. Similarly, there was no evidence of a dominant lethal effect in exposed male mice.